Morphofunctional changes following adenotonsillectomy of obstructive sleep apnea children: a case series analysis - Mariana M. Tinano; Helena M. G. Becker; Letícia P. Franco; Claudia P. G. dos Anjos; Vinícius M. Ramos; Carolina M. F. F. Nader; Joana Godinho; Henrique de Párcia Gontijo; Bernardo Q. Souki (Progress in Orthodontics, 2022)
Abstract Objective To perform a case series analysis of the changes in the pulmonary artery systolic pressure (PASP), nasal inspiratory flow (NIF), upper airway volume, obstructive apnea/hypopnea index (OAHI), and the maxillomandibular three-dimensional (3D) morphology after adenotonsillectomy (T&A) of obstructive sleep apnea children (OSA). Materials and methods Retrospective assessment of files from 1002 children screened between 2012 and 2020 in a hospital-based mouth-breather referral center. From this universe, 15 obstructive sleep apnea children (7 females; 8 males), ages 4.1 to 8.9 years old (mean age of 5.4 years ± 1.3), who presented indications of tonsillectomy and/or adenoidectomy were selected. The complete baseline examination (T0) was carried out before T&A and a second complete examination (T1) was made 18.7-month follow-up after T&A (ranging from 12 to 30 months). Eleven patients were submitted to T&A, and four patients had indications but did not receive authorization for surgery from the public health system. According to the protocol of the outpatient clinic for OSA patients, Doppler echocardiography, polysomnography, rhinomanometry, and computed tomography imaging was performed at (T0) and (T1). Results PASP decreased 16.6% after T&A. NIF increased more in T&A children (40.3%) than in non-T&A children (16.8%). The upper airway volume increased in T&A and non-T&A children, but greater volumetric gain (45.6%) was found in the nasopharynx of T&A patients. OAHI did not change in six T&A children (55%) and three non-T&A children (75%). The maxilla displaced downward and backward relative to the cranial base in six T&A children (55%) and two untreated children (50%). Nine of the T&A children (85%) and three untreated children (75%) presented extensive condylar growth and increased mandibular length. The qualitative 3D assessment showed similar morphological 3D changes in T&A and non-T&A patients. Conclusion Pulmonary artery systolic pressure decreased, nasal inspiratory flow increased, and nasopharynx volume increased following adenotonsillectomy, but obstructive apnea/hypopnea index and maxillomandibular morphology were similar in surgical and non-surgical patients.